Thermodynamics of slush and snow–ice formation in the Antarctic sea-ice zone. (September 2016) - Jutras, Mathilde; Vancoppenolle, Martin; Lourenço, Antonio; Vivier, Frédéric; Carnat, Gauthier; Madec, Gurvan; Rousset, Clément; Tison, Jean-Louis
Abstract: Snow over Antarctic sea ice is often flooded by brine or seawater, particularly in spring, forming slush and snow ice. Here, we evaluate the representation of the thermodynamics of slush and snow–ice formation in large-scale sea-ice models, using laboratory experiments (NaCl solutions poured into grated ice in an isolated container). Scaling analysis highlights latent heat as the main term of the energy budget. The temperature of the new sea ice immediately after flooding is found very close to the saltwater freezing point, whereas its bulk salinity is typically > 20 g / kg . Large-scale sea-ice models faithfully represent such physics, yet the uncertainty on the origin of flooding saltwater impacts the calculated new ice temperature, because of the different salinities of seawater and brine. The laboratory experiments also suggest a potential limitation to the existing physical representations of flooding: for brine fractions > 60 %, ice crystals start floating upon saltwater. Natural sea-ice observations suggest that the isolated system assumption holds for a few hours at most, after which rapid heat and salt exchanges mostly destroy the initial flooding signature on temperature and salinity. A small footprint on ice salinity remains however, natural snow ice is found 3–5 g/kg more saline than other forms of sea ice.